2016
DOI: 10.1097/brs.0000000000001659
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony-Stimulating Factor Improves Motor Function in Rats Developing Compression Myelopathy

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…We previously demonstrated that blood flow in the compressed segment is markedly reduced, indicating the presence of local spinal cord ischemia in the chronic compression myelopathy model [32]. Consistent with our previous studies [9, 10], this study also demonstrated that chronic spinal cord compression induces apoptotic cell death. In hypoxic stress conditions, endogenous EPO is produced in response to low oxygen partial pressure and protects neurons [34].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We previously demonstrated that blood flow in the compressed segment is markedly reduced, indicating the presence of local spinal cord ischemia in the chronic compression myelopathy model [32]. Consistent with our previous studies [9, 10], this study also demonstrated that chronic spinal cord compression induces apoptotic cell death. In hypoxic stress conditions, endogenous EPO is produced in response to low oxygen partial pressure and protects neurons [34].…”
Section: Discussionsupporting
confidence: 91%
“…Rotarod performance was assessed by using the rotarod device (ENV-557, Med Associates Inc., St. Albans, VT). Based on our previous research, a moderate rotation speed of 10 rpm was set [710]. All rats could walk on the rotarod for more than 300 seconds before surgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it has demonstrated a role in neuroprotection, neural tissue repair, and sensorimotor recovery [92]. In rat SCI models, it reduces cell apoptosis and promotes motor recovery [93,94].…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%